2021
DOI: 10.3390/foods10030516
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Extraction Methods to Recover Added-Value Compounds from Seaweeds: Sustainability and Functionality

Abstract: Seaweeds are a renewable natural source of valuable macro and micronutrients that have attracted the attention of the scientists in the last years. Their medicinal properties were already recognized in the ancient traditional Chinese medicine, but only recently there has been a considerable increase in the study of these organisms in attempts to demonstrate their health benefits. The extraction process and conditions to be used for the obtention of value-added compounds from seaweeds depends mainly on the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 112 publications
1
35
0
Order By: Relevance
“…e physicochemical analyses showed the pH in the range of 5.12-5.34. A similar study by Wagh et al found a pH of 1% aqueous solution within the range of 3.77-4.85, which was more acidic than our study [8]. e limit given by the pharmacopoeia for pH (1% aqueous solution) is in the range of 3.82-4.23. ough the pH of all of the selected brands was close to each other, they did not comply with the specification, and all were out of the limit.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…e physicochemical analyses showed the pH in the range of 5.12-5.34. A similar study by Wagh et al found a pH of 1% aqueous solution within the range of 3.77-4.85, which was more acidic than our study [8]. e limit given by the pharmacopoeia for pH (1% aqueous solution) is in the range of 3.82-4.23. ough the pH of all of the selected brands was close to each other, they did not comply with the specification, and all were out of the limit.…”
Section: Discussionsupporting
confidence: 52%
“…However, the safety and efficacy of herbal drugs depend upon the sources and the quality of raw materials such as storage and transportation, temperature, light exposure, drying, packing, age and parts of the plant collected, good manufacturing practices (GMP), contaminations such as microbial contamination, pesticide residues, intentional or unintentional adulteration with heavy metal, allopathic drugs such as steroids, and nonsteroidal anti-inflammatory drugs (NSAIDs), which can directly affect the quality and the therapeutic value of herbal medicines [8,9]. Hence, the quality control of the ayurvedic formulation using modern analysis techniques is very important [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the present work cladodes at a late maturity stage, which are considered as waste and have no commercial value, were used. Therefore, this is a sustainable extraction method [36].…”
Section: Yield and Separation Efficiency Of The Mucilage Extracted From Fresh And Dried O Ficus Indica Cladodesmentioning
confidence: 99%
“…The primary metabolites, which are directly involved in processes such as growth, development, reproduction to perform physiological functions, can be divided into several classes: carbohydrates (fucoidan, alginate, laminarin in brown seaweeds, agar, carrageenan in red seaweeds, and ulvan in green seaweeds), lipids (fatty acids: saturated, mono-, di-, and polyunsaturated, waxes, acylglycerols: mono-, di-, and triacylglycerols, phospholipids, glycoglycerolipids, fat-soluble vitamins, e.g., A and E, sterols, and carotenoids), and proteins (combination of different amino acids). In addition to the primary metabolites, seaweeds can accumulate minerals (microelements, macroelements, and trace elements) that are also essential to their life (Makkar et al 2016 ; Salehi et al 2019 ; Matos et al 2021 ). Seaweeds can also synthesize a vast number of secondary metabolites, which largely determine their bioactive potential (Øverland et al 2019 ; Salehi et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are formed in the biomass as a response to exposure to biotic (e.g., fungi, bacteria, viruses, insects, etc.) and abiotic stress (e.g., UV radiation, drought, salinity, high temperature) (Metsämuuronen and Sirén 2019 ; Matos et al 2021 ). An important group of seaweeds’ secondary metabolites are phenolics, which involve simple phenols like phenolic acids and polyphenols, including flavonoids and non-flavonoids – e.g., tannins.…”
Section: Introductionmentioning
confidence: 99%